2023
DOI: 10.1021/acsestengg.2c00424
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Machine Learning Combined with High-Throughput Computational Screening of Hydrophobic Metal–Organic Frameworks for Capture of Methanol and Ethanol from the Air

Abstract: The capture of low concentration alcohol VOCs (methanol and ethanol) from the air has also attracted more and more attention. In this work, high-throughput computational screening (HTCS) and machine learning (ML) methods based on molecular simulations were used to investigate the adsorption properties of methanol and ethanol in 31 399 hydrophobic metal–organic frameworks (MOFs). First, the structure–performance relationship of MOFs was successfully established through univariate analysis, and the key descripto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…The prediction accuracy of the AutoML‐DE model for various output parameters is evaluated by the root mean square error (RMSE) and determination coefficient ( R 2 ), which are defined as shown in Equations () and () 33 . R 2 is an indicator of the similarity between estimated and measured values, while RMSE serves as the standard deviation between predicted and true values and is widely used to measure the degree of difference between the two 20 RMSE=1nfalse∑i=1n()Yigoodbreak−Ytruêi2, R2=1false∑i=1n()Ytruêigoodbreak−trueY¯2false∑i=1n()Yigoodbreak−trueY¯2, where n is the number of samples; Yi and trueŶi represent the true and predicted values of the i th data; and Ytrue¯ denotes the average of the dataset.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The prediction accuracy of the AutoML‐DE model for various output parameters is evaluated by the root mean square error (RMSE) and determination coefficient ( R 2 ), which are defined as shown in Equations () and () 33 . R 2 is an indicator of the similarity between estimated and measured values, while RMSE serves as the standard deviation between predicted and true values and is widely used to measure the degree of difference between the two 20 RMSE=1nfalse∑i=1n()Yigoodbreak−Ytruêi2, R2=1false∑i=1n()Ytruêigoodbreak−trueY¯2false∑i=1n()Yigoodbreak−trueY¯2, where n is the number of samples; Yi and trueŶi represent the true and predicted values of the i th data; and Ytrue¯ denotes the average of the dataset.…”
Section: Methodsmentioning
confidence: 99%
“…Professor Teng Zhou's team 17–19 have employed this approach to analyze the operational efficacy of covalent organic frameworks in methane utilization, highlighting that AutoML can streamline the modeling process, enable automatic configuration of ML model parameters, and overcome the constraint of expert involvement. Similarly, Zhang et al 20 studied an AutoML algorithm to improve the prediction accuracy of the adsorption performance of metal‐organic frameworks. They found that the AutoML algorithm can not only enhance the reliability of prediction results, but also avoid overfitting in the model.…”
Section: Introductionmentioning
confidence: 99%
“…Since the range of data varies widely, the comparison will be inconsistent without normalization. Hence, this work used a row scale normalization from 1 to 10 approach in data processing, which has also been used in previous work . The unified units facilitated meaningful comparisons and analyses, ensuring the data set’s quality and integrity.…”
Section: Methodsmentioning
confidence: 99%
“…The AutoML can automatically select the suitable model to predict methane production and determine the related hyperparameters without artificial intervention. Meanwhile, AutoML can improve the reliability of prediction results by avoiding overfitting and other issues . However, the limited availability of data often restricts the application of data-driven models in anaerobic bioprocess research, especially in the context of novel bioprocess testing and initial experimental endeavors …”
Section: Introductionmentioning
confidence: 99%